Embracing the Other: A Christian response to counterterrorism legislation in Australia - Macallan, B. (Pacifica, 2015)
This article explores the impact of Australia’s counterterrorism legislation and its resulting influence on Muslim communities in Australia. It does this by exploring Australia’s participation in the war on terrorism and how the government and society have responded. It then seeks to use Miroslav Volf’s concept of embrace as a way for the Church to begin to overcome its own cultural bias, and to present an example to the wider culture in working against these negative effects. Specific actions and proposals are offered for the Australian context at each part of the embrace.